The Relationship of Drinking Water Depot Sanitation with the Presence of Coliform and Eschericia Coli - Asmawati Badun (MIRACLE Journal Of Public Health, 2021)
The coverage of sanitation in Indonesia, especially in drinking water, is known to have not been in accordance with the needs of the population. Likewise in Kendari District where drinking water facilities (depots) and the quality of the water produced do not meet health requirements. This study aims to determine the correlation of drinking water depot sanitation hygiene with the presence of Coliform and Eschericia Coli bacteria in Kendari District. The type of study is observational analytic with a cross-sectional study design. The study population, namely all drinking water depots in the working area of ​​the Kendari District, amounted to 14 depots with a simple random sampling of 13 depots. Testing the data using the Fisher's Exact Test. The results of the study on sanitation hygiene of the place obtained p-value=0.014 and phi test=0.822, the results of the test on hygiene and sanitation of equipment obtained p-value=0.014 and phi test=0.822, while the sanitation hygiene of the handlers obtained p-value=0.003 and phi test=1.000. This means that there is a strong relationship between sanitation hygiene of premises, equipment and handlers with the presence of Coliform and Eschericia Coli bacteria in Kendari District. It is hoped that health center will actively conduct counseling in order to increase public insight and knowledge about sanitation hygiene of places, equipment and handlers at drinking water depots.